Predictive value of lymphocyte to high-density lipoprotein cholesterol ratio for early mortality risk in patients with moderate-severe traumatic brain injury. - WANG, Zhao-yi; DU, Ran; LI, Wen-juan; ZHANG, Li-na; FANG, Yan-bo (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Objective To analyze the relationship between lymphocyte to high-density lipoprotein cholesterol ratio (LHR) and 28 d all-cause mortality after admission in moderate -severe traumatic brain injury (TBI) patients, and evaluate the predictive value of indicator for mortality risk in moderate-severe TBI patients. Methods Clinical data and initial LHR after admission of total 163 patients with moderate-severe TBI, who were first diagnosed at The First Affiliated Hospital of Zhengzhou University between January 1, 2020 and August 31, 2024, were collected. Univariate and multivariate stepwise Cox proportional hazards regression analyses were used to identify the influencing factors for 28 d all-cause mortality after admission in moderate-severe TBI patients. The predictive value of LHR was further validated by plotting receiver operating characteristic (ROC) curve and calculating the area under the curve (AUC). Results By the 28 d after admission, 128 patients (78.53%) survived, and 35 patients (21.47%) died. Multivariate stepwise Cox proportional hazards regression analysis: Model 1 (unadjusted for any confounding factors), Model 2 [adjusted for age, time from injury to admission, diabetes, and Glasgow Coma Scale (GCS) score at admission], and Model 3 (further adjusted for all potential confounding factors such as sex, cause of injury, and hypertension) all showed that a lower LHR was a risk factor for increased 28 d all-cause mortality after admission in moderate-severe TBI patients (HR = 0.028, 95%CI: 0.005-0.156, P = 0.000; HR = 0.048, 95%CI: 0.008-0.289, P = 0.000; HR = 0.032, 95%CI: 0.004-0.234, P = 0.000). The predictive value of LHR was further validated using the ROC curve, with AUC of 0.767 (95%CI: 0.681-0.854, P = 0.000). The optimal cutoff value was 0.460, with a sensitivity of 80.50% and a specificity of 62.90%. Conclusions The initial LHR after admission is a simple and easily accessible early predictor of 28 d all-cause mortality after admission in moderate-severe TBI patients.